Dampak Penambahan Fly Ash Batu Bara Terhadap Kinerja Balok Beton Bertulang Tunggal - Sukmawati, Yulinda; Muhtar, Muhtar; Ahmad, Hilfi Harisan (Universitas Trunojoyo Madura, 2024)
The Paiton Steam Power (PLTU) is an industry that uses coal as fuel. One of the wastes is fly ash. Fly ash can be used as a partial replace cement because it has pozzolanic properties. The aim of this research is to determine the effect of adding coal fly ash on the flexural capacity, stiffness, ductility, crack patterns and failure of single reinforced concrete beams. The test objects consisted of five cylinders and five beams in the proportions of 0% fly ash, 5% fly ash, 10% fly ash, 15% fly ash and 20% fly ash. The fly ash used is type C category. The beam testing uses a four-point loading method. Test results showed that beams containing 15% fly ash have higher performance than other proportions. The flexural capacity of beams containing 15% fly ash increases to 18.96%, ductility increases to 2.74% and stiffness decreases to 24.44% of normal concrete or 0% fly ash. The crack and failure patterns of beams in the proportion fly ash have the same pattern as normal concrete.